QT prolongation associated with azithromycin/hydroxychloroquine combination in treatment of COVID-19: a single centre study - Alrasheedi, Sami M.; Alothman, Bader; Alharbi, Ayman; Alkhdairi, Ahmad; Zeitouni, Mohammed; Alrashdi, Mousa N.; Almogbel, Abdulaziz; Alrashidi, Hanee M. (International Journal of Advances in Medicine, 2021)
Background: The long QT syndrome is characterized by prolongation of QT interval, which may lead to life-threatening cardiac arrhythmias. Objectives were to assess prevalence, quantity and severity of QTc prolongation with combined drugs (azithromycin and hydroxychloroquine) in adults COVID-19 patients treated on these agents at KFSHRC. And to characterize cardiac complications of QTc prolongation with combined drugs. Methods: A retrospective cohort study at KFSH&RC, in Riyadh, Saudi Arabia. Baseline and daily ECG was done until completion of duration as per KFSH&RC guidelines for management of Covid-19, QTc prolongation>500 or increase of at least 60 ms compared with the pre-drug baseline value, or presence of cardiac conductive complications (torsades de pointes). The QTc prolongation was defined as>470 for male and >480 for female as per American Heart Association. A risk score that has been validated by Tisdale et al, for prediction of QT prolongation drug-related in admitted patients in cardiac care unit. The study duration was specified as one month after study approval by Research Ethics committee. Results: A total of 74 patients were included in the study. The patients were distributed according to their risk score for prediction of QT prolongation as the following: low (67/74), medium (6/74), high (1/74). Two patients with medium risk were started on both azithromycin and hydroxychloroquine. one of them his baseline QT was 490, Azithromycin was stopped as QT reached 502. The second patient has QT baseline 471, after starting treatment; QT range was 472-475, hydroxychloroquine was stopped on day 4. None of them had torsades de pointes. Only one patient with low risk, no baseline QT was recorded, but QT was 499 on day three, so hydroxychloroquine was stopped. Repeated ECG showed: QT decreased to 478, no torsades de pointes. Conclusions: In this single centered-retrospective cohort, we noticed that a small percentage of patients developed QT prolongation with the use of this combination. With the increasing the risk of developing QT prolongation the number of the patient who developed the condition increased. We used Tisdale score which is a scoring system Identifying hospitalized patients at risk for QT interval prolongation could lead to interventions to reduce the risk of torsades de pointes validated in May 2013.5 None of our population developed significant cardiac complications of QTc prolongation with combined drugs.